The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1161/hypertensionaha.108.111302
|View full text |Cite|
|
Sign up to set email alerts
|

Restorative Effect of Atrial Natriuretic Peptide or Chronic Neutral Endopeptidase Inhibition on Blunted Cardiopulmonary Vagal Reflexes in Aged Rats

Abstract: Abstract-Arterial baroreflex function diminishes with age, but whether cardiopulmonary vagal reflexes are similarly altered with physiological aging has not been fully elucidated. In this study, predominantly cardiac high pressure mechanoreceptor-activated (ramp baroreflex) and cardiopulmonary chemoreceptor-activated (von Bezold-Jarisch reflex) vagal reflexes in conscious, instrumented rats were impaired by 30% to 40% (PϽ0.05) in 24-month-old (nϭ12) compared with 6-month-old rats (nϭ12). To determine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Additional studies in anesthetized canines demonstrated that ANPdependent decreases in monophasic action potential and effective refractory period are due to secondary autonomically mediated effects (33). Another study demonstrated that these vagal reflexes can be activated both by ANP infusion and by inhibiting its degradation by blocking NEP (26). The implication from the Hodgson-Zingman study is that in patients expressing fsANP, these vagal reflexes would be under more prolonged pressure because of the elevated levels of total ANP (wtANP ϩ fsANP), which would eventually lead to early onset atrial fibrillation.…”
Section: Discussionmentioning
confidence: 98%
“…Additional studies in anesthetized canines demonstrated that ANPdependent decreases in monophasic action potential and effective refractory period are due to secondary autonomically mediated effects (33). Another study demonstrated that these vagal reflexes can be activated both by ANP infusion and by inhibiting its degradation by blocking NEP (26). The implication from the Hodgson-Zingman study is that in patients expressing fsANP, these vagal reflexes would be under more prolonged pressure because of the elevated levels of total ANP (wtANP ϩ fsANP), which would eventually lead to early onset atrial fibrillation.…”
Section: Discussionmentioning
confidence: 98%
“…In animals, increased levels of NPs or chronic inhibition of NEP are able to prevent the progression of cardiac aging (158,159). Similarly, in humans, simultaneous inhibition of NEP and Ang-II type-1 receptor (AT1R) with LCZ-696 (which is composed by Valsartan and Sacubitril) has shown to reduce significantly mortality and hospitalization in patients with HF (160).…”
Section: Neurohormonal Factorsmentioning
confidence: 99%
“…Этот механизм, по-видимому, имеет отношение к феномену относительной или абсолютной (парадоксальной при гипотензии) брадикардии и проявляется даже при низких (негипотензивных) концентрациях ANP [7,77,84]. Важно, что введение ANP или увеличение его концентрации в циркулирующей крови, благодаря лекарственному воздействию (ингибитором нейтральной эндопептидазы), приводит к увеличению чувствительности кардиопульмональных вагусных рефлексов, включая рефлекс Бецольда-Яриша [320,321]. В то же время ANP обладает свойствами антагониста симпатической нервной системы, способного оказывать подавляющие эффекты на всех уровнях барорефлекторной дуги.…”
Section: Anp и Bnpunclassified